2016
DOI: 10.1177/1479972316661924
|View full text |Cite
|
Sign up to set email alerts
|

Does the COPD assessment test reflect functional status in patients with COPD?

Abstract: The aim of this study was to investigate whether the chronic obstructive pulmonary disease (COPD) assessment test (CAT) reflects the functional status of patients with COPD. Forty-seven patients underwent anthropometric assessment, spirometry, the 6-minute walk test (6MWT), the Glittre-activity of daily living (ADL) test (TGlittre), the London Chest ADL (LCADL) scale, and the CAT. The total score of the CAT correlated with 6MWT distance, TGlittre time spent, and LCADL %total (r ¼ À0.56, 0.52, and 0.78, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 36 publications
2
9
0
1
Order By: Relevance
“…14 TGlittre is responsive to PRP 10 and it is able to differentiate the functional capacity of patients with COPD from healthy individuals. 15 Also, it correlates with several other instruments for assessing functional status 10,16---19 and health status 20 of patients with COPD.…”
Section: Introductionmentioning
confidence: 90%
“…14 TGlittre is responsive to PRP 10 and it is able to differentiate the functional capacity of patients with COPD from healthy individuals. 15 Also, it correlates with several other instruments for assessing functional status 10,16---19 and health status 20 of patients with COPD.…”
Section: Introductionmentioning
confidence: 90%
“…The COPD Assessment Test (CAT) consists of a unidirectional questionnaire that considers the individual’s perception of the disease and reflects their functional status. 11 However, whether the CAT score (CATs) could estimate peak oxygen uptake (VO 2 ) in this population has never been investigated.…”
Section: Introductionmentioning
confidence: 99%
“… 6 It reflects the functional status of COPD patients quite well. 7 A systematic review supported the reliability and validity of the CAT and found that the tool is responsive to interventions, although the minimal clinically important difference (MCID) of 2 points is not well established. 8 , 9 Regarding the evolution of the CAT over time, only little data is available.…”
Section: Introductionmentioning
confidence: 99%